The development of fire risks assessment for heritage buildings: a case study of "The Residency", Kuala Lumpur - Khirani Abdul Hamid (Kulliyyah of Architectural and Environmental Design, IIUM, 2011)
This research is aim to develop risk assessment method for heritage building. Based on the works of previous researchers the method was refined with a technique known as Analytical Hierarchy Method (AHP). The original method, based on the opinion of single person, was also improved by using a panel of expert. The new method was then tested at "The Residency", which is the official resident and office of the first Prime Minister of Malaysia, Y.AM. Tunku Abdul Rahman Putra al-Haj. The 128 years old building is gazetted as heritage building under National Heritage Act (2005) and the building now is part of the exhibition in Memorial Tunku Abdul Rahman complex which was operated by Malaysian National Archives.